SMART RECOMMENDATION SYSTEM MODELING FOR BATIK USING THE CONTENT BASED RECOMMENDATION METHOD - Atina, Vihi; Purwanto, Eko; Mohd, Farahwahida (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Batik was an intangible cultural heritage recognized by UNESCO, with unique variations of motifs, colors, and philosophies in each region, both in Indonesia and Malaysia. The development of the fashion industry and e-commerce brought both opportunities and challenges, since users often had difficulties finding batik that matched their preferences, occasions, or symbolic needs. This research aimed to develop a smart recommendation system model for batik using the content-based recommendation method. The dataset consisted of batik data from Indonesia and Malaysia with attributes such as region of origin, dominant color, main motif, category, and usage. The system development method applied was Prototyping, which included the stages of requirement identification, quick design, and prototype construction. The results showed that the system was able to provide relevant recommendations according to user preferences. For example, when the user selected batik preferences with green color, leaf motif, and casual usage, the system recommended Batik Priangan from Indonesia with the highest similarity value of 0.75. These findings proved that the content-based approach successfully connected batik attributes with user needs. This research was expected not only to simplify the search for batik products in the digital era but also to contribute to the preservation of batik culture through the utilization of information technology.